Model Rantai Pasok Dan Nilai Tambah Gula Semut Kelapa (Studi Kasus: Kelompok Tani) - Siti Wardah (Jurnal Teknologi Agro-Industri, 2022)
Ant sugar is coconut sugar in the form of a powder made from sap, which is a solution of sap water that has been cooked so that it becomes sugar. This study aimed to improve the supply chain and added value of ant sugar through supply chain analysis and added value of ant sugar. The mechanism of the ant sugar supply chain was identified by a qualitative method. This research was conducted with a systems approach supported by the Hayami method to calculate added value. The added value and benefits obtained by farmers and SMEs are 84.43% and 64.58%, with profits of 51.1% and 39.59%, respectively. The added value of the owner of the production factor of direct labor income to farmers and IKM is 39.48% and 27.91%, respectively.